Mining and validating novel SSR markers based on coconut (Cocos nucifera L.) whole genome and their use for phylogenetic analysis - ANDI NADIA NURUL LATHIFA HATTA; DEWI SUKMA; ISMAIL MASKROMO; SUDARSONO SUDARSONO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hatta ANNL, Sukma D, Maskromo I, Sudarsono. 2022. Mining and validating novel SSR markers based on coconut (Cocos nucifera L.) whole genome and their use for phylogenetic analysis. Biodiversitas 23: 5122-5131. The coconut (Cocos nucifera L.) genome sequences were available at the chromosome level in 2019, and they can be used to develop the whole genome SSR markers. This study aimed to conduct in silico analysis of the whole coconut genome to mine SSR sequences, design SSR markers distributed across coconut chromosomes, validate the designed primers to generate SSR markers, and use them for the phylogenetic analysis of coconuts. The SSR loci were mined from publicly available coconut genomes. Targeted primers for amplifying 20 dinucleotide SSR loci were selected and used for phylogenetic analysis of coconuts. The SSR mining identified 543,774 dinucleotide repeat motifs across the coconut genome, and most of the dinucleotide SSRs are AG (46.18%) and AT (40.03%) repeats. Primer pairs targeted to amplify 876 SSR loci and distributed in 16 coconut chromosomes were successfully designed and deposited in a public data repository for public access. The 237 SSR primer loci were novel and could generate new SSR markers. Among 20 selected and tested primers, 18 produced SSR markers, and 15 pairs yielded polymorphic markers when used to evaluate 25 coconut accessions. The analysis showed that the designed SSR primers were informative for evaluating coconut genetic diversity and phylogenetic analysis.